2012
DOI: 10.1186/1477-7827-10-85
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical pharmacological profile of nomegestrol acetate, a synthetic 19-nor-progesterone derivative

Abstract: BackgroundNomegestrol acetate (NOMAC), a synthetic progestogen derived from 19-nor-progesterone, recently completed clinical trials for use with 17beta-estradiol in a new monophasic combined oral contraceptive. In this review, published as well as previously unpublished preclinical studies that detail the effects of NOMAC on estrogenic, progestogenic, and androgenic systems, as well as mineralocorticoid, glucocorticoid, bone, and metabolic indices are described.MethodsIn vitro assays to determine NOMAC structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…NOMAC is a synthetic 19-nor-progesterone derivative [9] . It is a progesterone receptor (PR) agonist that almost exclusively binds to progesterone receptors in hormone-sensitive cells derived from rats and humans [9] .…”
Section: Pharmacologymentioning
confidence: 99%
“…NOMAC is a synthetic 19-nor-progesterone derivative [9] . It is a progesterone receptor (PR) agonist that almost exclusively binds to progesterone receptors in hormone-sensitive cells derived from rats and humans [9] .…”
Section: Pharmacologymentioning
confidence: 99%
“…NOMAC was able to inhibit estrone sulfatase and 17β-hydroxysteroid dehydrogenase activity, 2 enzymes responsible for the conversion of E1S to E2. 66 In vitro studies have shown that NOMAC blocks the conversion of estrone sulfate to estradiol in MCF-7 and T47-D hormone-dependent breast cancer cell lines. 67 According to the global proliferative measurements, NOMAC had a similar or better antiproliferative effect than LNG and DRSP.…”
Section: Nomegestrol Acetate (Nomac)mentioning
confidence: 99%
“…It has high affinity and selectivity for human progesterone receptor (PR) and is devoid of any estrogenic, androgenic, glucocorticoid or mineralocorticoid activity. In addition, it has excellent anti‐gonadotropic activity, good progesterone receptor‐mediated anti‐estrogenic activity, and moderate anti‐androgenic activity . NOMAc has been approved and marked by commercial names such as Zoley ® , Lutenyl ® , Uniplant ® , Naemis ® , etc.…”
Section: Introductionmentioning
confidence: 99%
“…The solution was stirred at refluxing for 4 h, cooled to rt and poured onto ice-water, extracted with dichloromethane, washed with brine, dried over sodium sulfate.The solvent was removed in vacuo and the residue was purified by a silica gel column to give 7 (3.5 g, yield 67%, HPLC 98.8% at 254 nm). CDCl3 , ppm): δ 124.37, 52.34, 50.35, 48.32, 41.42, 38.31, 37.31, 36.36, 30.91, 30.31, 26.76, 25.71, 23.47, 21.26, The solution was poured into water, extracted with dichloromethane, washed with brine, and dried over sodium sulfate. The solvent was removed in vacuo and the residue was purified by a silica gel column to give impurity B (1.2 g, yield 40%, HPLC 99.73 2H), 0.74 (s, 3H); 13 C NMR (CDCl 3 , ppm): δ 203.94, 200.17, 170.69, 156.57, 139.84, 135.32, 121.47, 96.45, 62.78, 48.53, 47.52, 45.32, 41.00, 40.09, 37.40, 30.98, 30.31, 26.85, 26.45, 24.93, 23.19, 21.20, 14.20; ESI-MS: m/z 387.2146 [M+1] + ; calcd.…”
mentioning
confidence: 99%